The Effect Of Iron Addition And Tungsten Content On The Corrosion Resistance Of W-Pre Alloy Brass Composite - Rozi Bin Ewol (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
In this project, the W-pre alloy brass composite is prepared through compacting method of powder metallurgy. Different composition of brass and tungsten was prepared and samples with iron addition sintered together using Liquid phase sintering techniques under protective atmosphere. The density of the samples after sintering affected by the volume fraction of tungsten and brass. More tungsten with iron addition increases the hardness of the samples after sintering. While increasing the hardness, addition of iron accelerate the corrosion rate of the samples. The increasing volume fraction of tungsten decrease the corrosion rate of the samples.